Effect of Nidra on Meda Dhatu with special reference to Different Dehaprakriti (International Journal of Ayurveda and Pharma Research, 2024)
According to Ayurveda, sleep is included in Upastambha Traya, Adharaniya Vega hence it sustains life. Getting enough Nidra helps in maintaining normal growth and development of the body. According to Ayurveda, improper sleep (Nidra Viparyaya) may cause some life style diseases (Sthaulya). So, it can be said that abnormal, inadequate Nidra can make a person Atura (diseased). Among the seven Dhatus, Meda with Jala and Prithvi as its dominant elements, is solid and soft. It is the storage site for excess fat in the body. Definition of Swastha also refers to the moderate quantity of the seven Dhatus of the body. Disorders may develop if there is variation in it. In this context, the excess accumulation of Meda Dhatu that is Medo Vruddhi results in overweight/obesity and decrease in Meda Dhatu that is Meda Kshaya results in underweight. Nidra has such inevitable effects on mind and body. In Ayurveda, Acharya Charak has stated in Charak Sutrasthan, Adhyay 21/51 “Swapnahar Samutthe Cha Sthaulya Karshye Visheshatah” that means Aahar and Nidra are the main causes for Sthaulya and Karshya. Also, modern science has stated that sleep requirement is not constant but has to be taken as per the persons need. Therefore, to sum up, In, today’s era, sleep is seen to be majorly disturbed which is one of the reasons for psychosomatic disorders. There is disturbed fat distribution observed in people surrounding us with no major co-morbidity but still showing symptoms related to Meda Dhatu. Therefore, to reveal the role of Nidra to cause the improper Meda dhatu distribution in body So, this study is being carried to explore the effect of Nidra on Meda Dhatu with special reference to different Deha Prakriti.